Clinical Predictors of the Risk of Early Colectomy in Ulcerative Colitis: A Population-based Study. Issue 8 (17th July 2017) - Al-Darmaki, Ahmed; Hubbard, James; Seow, Cynthia H.; Leung, Yvette; Novak, Kerri; Shaheen, Abdel Aziz; Panaccione, Remo; Kaplan, Gilaad G.
Abstract : Background: A subset of patients with ulcerative colitis (UC) will require colectomy within a few years of diagnosis. Thus, our aim was to determine the clinical predictors of early colectomy among patients with UC who are hospitalized with an acute flare. Methods: Using population-based surveillance (1996–2009), all adults (≥18 years) hospitalized for UC within 3 years of diagnosis (n = 489) were identified. The primary outcome was a colectomy within 3 years of diagnosis. All medical charts were reviewed. A logistic regression model evaluated clinical variables that predicted colectomy within 3 years of diagnosis, and adjusted odds ratios (ORs) with 95% confidence intervals (CIs) were reported. Results: Among patients admitted to hospital with UC within 3 years of diagnosis, 57.7% underwent colectomy, with the odds of colectomy decreasing by 12% per year. Early colectomy was more likely among patients aged 35 to 64 years versus 18 to 34 years (OR 2.18 [95% CI, 1.27–3.74]), males (OR 2.03 [95% CI, 1.24–3.34]), those with pancolitis (OR 5.38 [95% CI, 3.20–9.06]), and living in rural areas (OR 2.81 [95% CI, 1.49–5.29]). Prescription of infliximab before hospitalization increased odds of surgery (OR 5.12 [95% CI, 1.36–19.30]). Conclusions: Patients hospitalized for UC have a high risk of early colectomy. This is particularly true in middle-aged men, those living in rural areas, and those without response to infliximab.